2000
DOI: 10.1148/radiology.215.2.r00ma38520
|View full text |Cite
|
Sign up to set email alerts
|

Reperfused Rat Myocardium Subjected to Various Durations of Ischemia: Estimation of the Distribution Volume of Contrast Material with Echo-planar MR Imaging

Abstract: The fDV of MR contrast material in the periinfarcted rim was significantly (P <. 05) greater than that in the normal myocardium, but significantly less than that in the core of infarcted myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
118
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 38 publications
12
118
0
Order By: Relevance
“…Table 1 summarizes these previous findings from other groups. Specifically, the estimates of v e from this study are similar to v e results from autoradiographic imaging and histological sectioning techniques (29)(30)(31) and are comparable to v e estimates from the steady-state Ct/Cb method, using regional changes in signal enhancement (7,9,10,32). v e measurements from histological studies range from 19%-30% depending on the method of chemical fixation and histological analysis.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Table 1 summarizes these previous findings from other groups. Specifically, the estimates of v e from this study are similar to v e results from autoradiographic imaging and histological sectioning techniques (29)(30)(31) and are comparable to v e estimates from the steady-state Ct/Cb method, using regional changes in signal enhancement (7,9,10,32). v e measurements from histological studies range from 19%-30% depending on the method of chemical fixation and histological analysis.…”
Section: Discussionsupporting
confidence: 76%
“…One limitation of the study is that when computing v e and Ct/Cb, the vascular blood volume was assumed to be a constant Vb=0.04, which was the mean model estimate of Vb from all of the dynamic contrast-enhanced perfusion studies. While this value of Vb is comparable to values found by another group using MRI (18,29), it is lower than estimates of Vb found by some histopathological estimates (30,31), and it may be possible that within a region of myocardium the fraction of tissue comprised of blood vasculature may not be spatially uniform.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Ischemically injured myocardium after 30 minutes of occlusion is expected to contain viable and nonviable portions. 22 Two groups were studied (nϭ8 rats per group). Group 1 animals received 0.3 mmol/kg Gd-DTPA on day 1 (2-hour reperfusion) and on day 2 (24-hour reperfusion) and were imaged after each injection.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Its slow clearance, however, is favorable for measurement of extracellular space and assessment of myocardial viability. Arheden et al (21,22) and Pereira et al (23,24) demonstrated that the increase of the fraction of nonviable myocytes is paralleled by an expansion of the extracellular distribution volume from 18% in normal myocardium and Ͼ 80% in infarcted myocardium (21). Measuring the extracellular space with a rapidly clearing standard extracellular contrast agent, however, is difficult (25,26).…”
Section: Extracellular Contrast Mediamentioning
confidence: 99%